Disentangling the effects of genotype and environment on growth and wood features of Balfourodendron riedelianum trees by common garden experiments in Brazil - da Silva, Jane Rodrigues [UNESP]; Rossi, Sergio; Khare, Siddhartha; Longui, Eduardo Luiz; Marcati, Carmen Regina [UNESP] (MDPI, 2020)
Intraspecific studies with populations replicated in different sites allow the effects of genotype and environment on wood features and plant growth to be distinguished. Based on climate change predictions, this distinction is important for establishing future patterns in the distribution of tree species. We quantified the effects of genotype and environment on wood features and growth of 30-year-old Balfourodendron riedelianum trees. We used three provenances planted in two common garden experiments with difference in precipitation and temperature. We applied linear models to estimate the variability in wood and growth features and transfer functions to evaluate the responses of these features to temperature, precipitation, and the standardized precipitation evapotranspiration index (SPEI). Our results showed that genotype had an effect on vessels and rays, where narrower vessels with thinner walls and larger intervessel pits, and shorter, narrower and more numerous rays were observed in provenances from drier sites. We also observed the effect of the environment on wood features and growth. Trees growing in the wetter site were taller and larger, and they had wider vessels with thicker walls and lower ray density. Transfer functions indicated that an increase in temperature results in larger vessels with thicker walls, taller and denser rays, shorter and narrower fibers with thinner walls, and lower wood density. From a functional perspective, these features make trees growing in warmer environments more prone to drought-induced embolisms and more vulnerable to mechanical damage and pathogen attacks. Tree growth varied with precipitation and SPEI, being negatively affected in the drier site. Overall, we demonstrated that both genotype and environment affect wood features, while tree growth is mainly influenced by the environment. Plastic responses in hydraulic characteristics could represent important functional traits to mitigate the consequences of ongoing climate change on the growth and survival of the species within its natural range.
Keywords: Common garden; Drought; Phenotypic plasticity; Provenance test; Transfer functions